Effect of an interlayer on the emission characteristics of a white-light-emitting electroluminescent device with a Pr and Ce doubly sloped ZnS phosphor layer - Lee, YH; Ju, BK; Song, MH; Hahn, TS; Oh, MH; Kim, DH (AMER INST PHYSICS, 1996)
We have investigated light-emission characteristics of a white-light-emitting electroluminescent device with a doubly doped ZnS:Pr,Ce,F phosphor layer. We found that optimum codoping of Ce enhances the emission characteristics compared to the electroluminescent device with a singly doped ZnS:Pr,F layer. We also found that introducing an additional thin-insulating SixNy interlayer between the lower insulating layer and the phosphor layer significantly stabilizes the aging characteristics and improves the luminous efficiency. (C) 1996 American Institute of Physics.
Keywords: EFFICIENCY